"It's Overwhelming With the Grief" A Qualitative Study of Families' Experiences When a Young Relative Dies of Sudden Cardiac Death. Issue 4 (4th April 2023) - Allan, Katherine S.; Mason, Katherine L.; Garner, Jodi; Dainty, Katie N.; Huyer, Dirk; Cunningham, Kris; Dorian, Paul; Lewis, Krystina B.
Abstract : Background: Sudden cardiac death (SCD) in younger individuals is frequently caused by heritable cardiac conditions. The unexpected nature of SCD leaves families with many unanswered questions and an insufficient understanding of the cause of death and their own risk for heritable disease. We explored the experiences of families of young SCD victims upon learning about their relative's cause of death and how they perceive their own risk for heritable cardiac conditions. Methods: We conducted a qualitative descriptive study, by interviewing families of young (ages 12–45) SCD victims, who died between 2014 and 2018 from a heritable cardiac condition and were investigated by the Office of the Chief Coroner of Ontario, Canada. We used thematic analysis to analyze the transcripts. Results: Between 2018 and 2020, we interviewed 19 family members, of which 10 were males and 9 were females, ages ranging from 21 to 65 (average 46.2±13.1). Four main themes were revealed, each representing a distinct time period that families experience along a trajectory: (1) interactions between bereaved family and others, in particular coroners, shaped their search for answers about their relative's cause of death, with the types, formats, and timing of communication varying by case; (2) searching for answers and processing the cause of death; (3) incidental implications of the SCD event, such as financial strain and lifestyle changes contributed to cumulative stress; (4) receiving answers (or not) and moving forward. Conclusions: Families rely on communication with others, yet the type, formats, and timing of information received varies, which can influence families' experiences of processing the death (and its cause), their perceived risk and their decision to pursue cascade screening. These results may provide key insights for the interprofessional health care team responsible for the delivery and communication of the cause of death to families of SCD victims.